Education about worms through animated videos for early childhood - Ana Amalia; milda, ratna; Fendy Prasetyawan; Yuneka Saristiana; Isma Oktadiana; Arsiaty Sumule (Amaluna: Jurnal Pengabdian Masyarakat, 2024)
This worm disease can infect all ages, but those who are most susceptible to infection are children under five and elementary school age (SD) aged 5 to 14 years. To be able to break the chain of worm infections and reduce the number of worm infections in schools, this can be done by providing information or education. Providing education about worms can increase students' knowledge regarding preventing worms. The aim of this activity is to increase the knowledge of students and girls in preventing worms. The method of this service is to provide education using animated video media about worm disease and hand washing demonstrations. After counseling and demonstrations, the results of the education that has been provided will be evaluated using a questionnaire to evaluate students' knowledge of worms and their prevention after 1 week of providing counseling via educational video media. The results of the activity showed an increase in knowledge and psychomotor skills after being given education regarding worms and washing hands. It is hoped that increasing understanding of the dangers of worms can foster awareness and independence in preventing worms in families and communities. Keywords: Worms, education, animated video